Practical guide to thesis and dissertation writing - Rivera, Maximiano Marquez, Jr.; Rivera, Roela Victoria (Quezon City, Philippines : Katha Publishing Co, Inc., 2007)
Almost everyone in the academe has at one time or another prepared a report, a term paper or a thesis. Those who are working for advance degrees have the opportunity to prepare a dissertation or professional project paper. In most cases, the biggest challenge for everyone is how to begin to write and how to continue in the process to complete a research paper of acceptable quality and significance.
Part One. The Preliminaries -- Chapter 1. basic considerations in preparing the thesis and dissertation -- Chapter 2. The Nature and purpose of research -- Chapter 3. Sources, criteria and selection of a research problem -- Chapter 4. Preparing the research proposal -- Chapter 5. Thesis and dissertation format -- Part Two. Writing the research paper -- Chapter 6. Introduction to the research study -- Chapter 7. Theoretical framework -- Chapter 8. Methodology -- Chapter 9. Presentation, analysis and interpretation of data -- Chapter 10. Summary, conclusion and recommendation -- Chapter 11. Planning, developing and writing grant proposal.
Includes bibliographical references.
Keywords: DISSERTATION